Indonesian online media construction of American elected President, Donald Trump - Al Makmun, Muhammad Taufiq; Karunia Purna Kusciati,; Fenty Kusumastuti, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study aims to look at how online media in Indonesia construct Donald Trump's image as the elected president of the United States of America (USA). This research is a qualitative descriptive study using transnational American studies and historical approaches which also employs framing and media construction of reality theory. Framing and media construction of reality are employed to see how the media construct Trump's image to affect the Indonesian readers in terms of perceiving the image of Trump. The transnational study is used to see how the USA has influenced foreign countries, focusing on Indonesia. The inauguration of the USA’s president is significant for the Indonesian media and society and therefore, there is an impending need to review and drive opinions on the construction of Trump's image. In contrast, the historical approach is used to see how the media associate Trump with the history in the USA. Two online media: Kompas and Media Indonesia, provide the research data. The sample was taken from articles published a week before and a week after his inauguration address on January 20th, 2017. The finding shows that there are six issues used as frames in both of the online newspapers. They are (1) the consequences of Trump's appointment, (2) rejection of Trump’s leadership, (3) Trump vs. Obama, (4) Trump and the media, (5) Trump’s concept of Make America Great Again (MAGA), and (6) the celebration of Trump’s inauguration. Trump is constructed as a popular figure through his rhetoric. His capability as a president is, however, questioned.